Implementation of National Defense in the Modern Era: Challenges and Strategies to Support National Security - Juniusyani, Zhafirah Azzahra; Syahtaria, Moh Ikhwan; Abriansyah, Tri Panca Titis; Widodo, Pujo; Sukendro, Achmed (CV. Rayyan Dwi Bharata, 2025)
Implementing National Defense in the modern era has its own challenges in supporting national security. In the modern era full of security dynamics and challenges, the role of technology and innovation is crucial in supporting national security strategies. This research aims to explain how technology has changed the security paradigm, discussing key aspects such as monitoring and detection, communication and information, cyber strategy, and the development of modern weapons. The research method used is a narrative review type literature review method with data collection techniques using Publish or Perish and Google Scholar. The research results show that the use of advanced technologies such as AI, sensors and encrypted communication systems has provided significant advantages in dealing with complex threats. The research method used is a quantitative approach with a literature review design. The findings show that the challenges in implementing National Defense are not easy because there are several factors that influence the implementation of National Defense and strategies that support national security. The conclusion of this article is that technology in the modern era has advantages in supporting national security and facing non-military threats.